EDITORIAL MANAGEMENT OF THE NEWS PROGRAM “TREAT SEPINCUK NEWS” AT JTV MADIUN - Ashari, Mutia Kultsum (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Abstract: Television media is a very potential media. As a medium in the form of audio-visual, television is able to seize 94% of the channel for the entry of messages and information to individuals. The easy dissemination of information through television media, especially news, makes ordinary people believe all the news displayed in the television. Therefore, it is necessary to know the production process of television media, especially beirta programs that most often affect the public. This study aims to find out how the editorial management system of SSB news programs at JTV Madiun. Data collection techniques in this study included interviews, observations, and documentation, with analysis using the Miles and Hubermand model. And honed with the knife of analysis, namely peter pringgless's mass media theory where there are 4 steps, namely Planning, Organizing, Implementing, and Evaluating. The approach taken by the researcher is a descriptive qualitative approach. The results of the study were obtained: 1) SSB planning is carried out unsystematically, so that it can cause miscommunication, 2) SSB organizing is in accordance with the theory by placing employees according to their abilities, 3) the production stage is well implemented, so that there are rarely obstacles, 4) Evaluation is rarely carried out, so that employees do not know the development of the SSB program.